Utilization Patterns of a Clinic‐Based Food Referral Program: Findings from the Mid‐Ohio Farmacy. (15th September 2021) - Walker, Daniel; DePuccio, Matthew; Hefner, Jennifer; Garner, Jennifer; Joseph, Joshua; Headings, Amy; Clark, Aaron
Abstract : Research Objective: Evidence suggests that clinic‐based food referral programs (FRP) offer health benefits to food insecure patients, yet little attention has been paid to understanding patient utilization of such programs. Our study addresses this gap by reporting on the patient characteristics associated with uptake and utilization of a FRP—the Mid‐Ohio Farmacy (MOF). The MOF is a partnership between a Midwestern regional foodbank and local healthcare providers, including a large, academic medical center (AMC). The MOF uses a variation on food vouchers: an electronic referral from a patient's primary care provider to one of 14 partner food pantries in the metropolitan area. Referred patients who visit a participating pantry are eligible to receive fresh produce once weekly. Study Design: This observational study leverages data from two AMC family medicine clinics offering the MOF referral from September 2019 to November 2020. Using multivariable logistic regression, we examined the association between filling a MOF referral (i.e., pantry visitor vs. non‐visitor) and patient demographic and clinical characteristics. Patients and their pantry visits were characterized based on their pre‐referral utilization (i.e., new or existing patrons; pre‐ or post‐referral pantry visit) to assess patterns of pantry utilization. Population Studied: AMC patients 18 years or older who screened positive for food insecurity and had an eligible chronic condition. Eligible conditions included a diagnosis of diabetes with hemoglobin A1c (HbA1C) >9%, obesity (BMI ≥ 30 kg/m 2 ), or hypertension; uncontrolled diabetes defined as a HbA1C > 9% with or without a diabetes diagnosis; or uncontrolled hypertension defined as blood pressure > 140/90 with a hypertension diagnosis. Principal Findings: In total, 51% (164/322) of patients who received a MOF referral visited a pantry at least once during the study period. Three factors were associated with an increased likelihood of filling a MOF referral: a 1‐year increase in age (0.7%; p < 0.01); diabetes diagnosis (11%; p < 0.05); and pantry visits prior to referral (36%; p < 0.001). Patients with uncontrolled hypertension were 19% (p < 0.001) less likely to visit a pantry following their referral. Relative to new visitors, existing visitors had a greater total number of visits following referral, shorter days to their first visit following referral, and travelled shorter distances. Existing visitors had more total pantry visits and more produce‐specific visits in the 90‐days following their referral relative to the 90‐days prior to their referral. Conclusions: Our results suggest that while the MOF can connect patients to food resources, further attention may be needed to encourage its use among patients who have not previously accessed pantries. Implications for Policy or Practice: Changes to the MOF program may be necessary such as adding one additional question to the food insecurity screening process (e.g., "Have you used a food pantry in the last year?"), so that potential first‐time users could be targeted for resources (e.g., transportation support such as Lyft credits or bus passes) to address barriers to pantry use. Additionally, reminding patients about the opportunity to visit the pantry, for instance through text message reminders or secure health portal messages, could help encourage patients to use this community resource. Primary Funding Source: Crisafi‐Monte Foundation.